EFFECT OF EXOGENOUS FIBROLYTIC ENZYMES ON PERFORMANCE OF LOCAL MALE GOATS - S. Khalifa; S. Khalaf (مجلة الأنبار للعلوم الزراعية, 2021)
The study was carried out at the Ruminant Researches Station, Department of Livestock Research, and Section of Agricultural Research, in the district of Abu Ghraib / Baghdad.  The objective of this study was to assess the effect of exogenous fibrolytic enzyme (EFE) (Safizym®- France) on the performance of local male goats. The study included two experiments: Experiment 2 (Nutritional Trail), the experiment was conducted during the period from 22 May 2017 to 17 July 2017. Eighteen males of local goats aged 4-5 months were used in this experiment. The animals were randomly assigned to three equal groups (6 animals/group). The first group (control) without enzyme, the second group (T1) treated with the EFE of 500g/ton of concentrate feed, the third group (T2) treated with the EFE of 1000g/ ton of concentrate feed. Experiment 2 (Digestion Trail), The digestion trail continued for a week during the period from 22 July 2017 until 28 July 2017. In this trail, nine local male goats were used. Three males from each group from experiment 1 were selected and submitted to the same previous treatments. The results showed no significant differences in body weight among the treatments during the duration of the experiment as well as between the weeks within the same treatment as a result of treatment with EFE of 500 g/ ton and 1000 g/ ton of concentrate feed. There were no significant effect on dry matter intake, daily weight gain and feed conversion efficiency. The results of the second experiment showed no significant effect of the treatment with EFE in the digestion coefficient of all nutrients as well as the total digestible nutrients.